Intellectual heritages of post-1990 public sector accounting research: an exploration. Issue 8 (30th June 2020) - Bruns, Hans-Jürgen; Christensen, Mark; Pilkington, Alan
Abstract : Purpose: The article's aim is to refine prospects for theorising in public sector accounting (PSA) research in order to capture the methodological benefits promised by its multi-disciplinarity. Design/methodology/approach: The study primarily employs a bibliometric analysis of research outputs invoking New Public Management (NPM). Applying a content analysis to Hood (1991), as the most cited NPM source, bibliographic methods and citation/co-citation analysis for the period 1991 to 2018 are mobilised to identify the disciplinary evolution of the NPM knowledge base from a structural and longitudinal perspective. Findings: The analysis exhibits disciplinary branching of NPM over time and its imprints on post-1990 PSA research. Given the discourse about origins of NPM-based accounting research, there are research domains behind the obvious that indicate disciplinary fragmentations. For instance, novelty of PSA research is found in public value accounting, continuity is evidenced by transcending contextual antecedents. Interestingly, these domains are loosely coupled. Exploring the role of disciplinary imprints designates prospects for post-NPM PSA research that acknowledges multi-disciplinarity and branching in order to deploy insularity as a building block for its inquiries. Research limitations/implications: Criteria for assessing the limitations and credibility of an explorative inquiry are used, especially on how the proposal to develop cumulative knowledge from post-1990 PSA research can be further developed. Practical implications: A matrix suggesting a method of ordering disciplinary references enables positioning of research inquiries within PSA research. Originality/value: By extending common taxonomies of PSA intellectual heritages, the study proposes the 'inquiry-heritage' matrix as a typology that displays patterns of theorisation for positioning an inquiry within PSA disciplinary groundings.